MiR-520h Stimulates Drug Resistance to Paclitaxel by Targeting the OTUD3-PTEN Axis in Breast Cancer. (11th May 2020) - Geng, Wenwen; Song, Haiyun; Zhao, Qianqian; Dong, Ke; Pu, Qian; Gao, Haidong; Lv, Yanrong
Abstract : MicroRNAs (miRNAs) have been identified as negative posttranscriptional regulators of target genes and are involved directly in the pathological processes of tumors, including drug resistance. However, the exact function of miR-520h in breast cancer remains poorly understood. The aim of this study was to investigate the molecular mechanisms of miR-520h in paclitaxel resistance in the MCF-7 breast cancer cell line. Ectopic expression of miR-520h could promote the proliferation of breast cancer cells and inhibit paclitaxel-induced cell apoptosis. Inhibiting the expression of miR-520h could enhance the sensitivity to paclitaxel in paclitaxel-resistant MCF-7/Taxol cells. Furthermore, luciferase reporter assays showed that OTUD3 was a direct target of miR-520h. OTUD3 plays a necessary role in the paclitaxel resistance effect of miR-520h, and cotreatment with a miR-520h inhibitor and OTUD3 overexpression significantly enhanced MCF-7 cell sensitivity to paclitaxel. Moreover, miR-520h substantially inhibited the protein expression of PTEN via OTUD3 and subsequently affected downstream p-AKT pathway activity. In a clinical study, we also found that high miR-520h expression was associated with more aggressive pathological characteristic and poor prognosis. Therefore, our findings showed that miR-520h targeted the OTUD3-PTEN axis to drive paclitaxel resistance, and this miR might be an important potential target for breast cancer treatment.